PERAN DARI DIMENSI BRAND EXPERIENCE RESTORAN DALAM MENCIPTAKAN BRAND LOYALTY DAN DAMPAKNYA TERHADAP BRAND EQUITY [THE ROLE OF THE RESTAURANT BRAND EXPERIENCE DIMENSION IN CREATING BRAND LOYALTY AND ITS IMPACT ON BRAND EQUITY] - Brittney E. D. Halik; Cindy Octavia; Jefta Julian; Margaretha Pink Berlianto (Indonesian Marketing Journal, 2021)
The purpose of this study is to investigate the effect of brand experience’s dimension which is sensory, affective, behavioral, and intellectual experience on the dimensions of customers’ brand loyalty (willingness to pay more, word of mouth, and repurchase intention) and its impact towards brand equity at the Sushi Tei restaurant located in Supermal Karawaci. This study uses quantitative approach and the data is gathered through the distribution of questionnaire with a sample of 260 respondents. The qualifications of the respondents are customers who ate at Sushi Tei restaurant at least once within the last three months. This study uses a non-probability sample design – purposive sampling. The analysis process used Partial Least Squares-Structural Equation Modeling. The analysis result shown that sensory experience, affective experience, behavioral experience, dan intellectual experience have positive effect on willingness to pay more and word of mouth. Affective experience and intellectual experience have positive effect on repurchase intention. Willingness to pay more, word of mouth and repurchase intention have positive effect on brand equity.  However sensory experience and behavioral experience have no effect repurchase intention.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk menginvestigasi pengaruh dimensi-dimensi dari brand experience yaitu sensory, affective, behavioral, dan intellectual experience terhadap dimensi-dimensi dari brand loyalty (willingness to pay more, word of mouth, and repurchase intention) and pengaruh dimensi dari brand loyalty tersebut terhadap brand equity pada restoran Sushi Tei yang berlokasi di Supermal Karawaci. Terdapat 15 hipotesis pada penelitian ini. Penelitian ini menggunakan pendekatan kuantitatif di mana data diperoleh dengan menyebarkan kuisioner sebanyak 260. Penelitian ini menggunakan purposive sampling dengan kriteria individu yang pernah bersantap di Sushi Tei Supermall Karawaci sebanyak sekali dalam kurun waktu tiga bulan terakhir. Metode analisis data menggunakan PLS-SEM. Hasil penelitian menunjukkan bahwa sensory, affective, behavioral, dan intellectual experience berpengaruh positif terhadap Willingness to pay more dan word of mouth.  Affective experience dan intellectual experience berpengaruh positif terhadap repurchase intention. Willingness to pay more, word of mouth dan repurchase intention berpengaruh positif terhadap brand equity. Akan tetapi sensory experience dan behavioral experience tidak berpengaruh positif terhadap repurchase intention.